Understanding and Measuring the Wellbeing of Carers of People With Dementia - Cunningham, Nicola A (Gerontologist, 2019)
BACKGROUND AND OBJECTIVES: To determine how the wellbeing of carers of people with dementia is understood and measured in contemporary health research. RESEARCH DESIGN AND METHODS: A systematic review of reviews was designed, registered with PROSPERO, and then conducted. This focused on systematic reviews of research literature published from 2010 onwards; with the wellbeing of carers of people with dementia being a primary focus. N = 19 studies met the inclusion criteria. Quality appraisal was conducted using the AMSTAR tool (2015). A narrative synthesis was conducted to explore how wellbeing is currently being understood and measured. RESULTS: Contemporary health research most frequently conceptualizes wellbeing in the context of a loss–deficit model. Current healthcare research has not kept pace with wider discussions surrounding wellbeing which have become both more complex and more sophisticated. Relying on the loss–deficit model limits current research in understanding and measuring the lived experience of carers of people with dementia. There remains need for a clear and consistent measurement of wellbeing. DISCUSSION AND IMPLICATIONS: Without clear consensus, health professionals must be careful when using the term “wellbeing”. To help inform healthcare policy and practice, we offer a starting point for a richer concept of wellbeing in the context of dementia that is multi-faceted to include positive dimensions of caregiving in addition to recognized aspects of burden. Standardized and robust measurements are needed to enhance research and there may be benefit from developing a more mixed, blended approach to measurement.